Study of a Compact Operator (International Journal of Scientific Research in Science and Technology, 2024)
In this present paper, we studied a compact operator. The purpose of this paper is to first review some concepts from Functional Analysis and Operator Algebra, then to apply these concepts to an in-depth introduction to Compact Operators and the Spectra of Compact Operators, leading to The Fredholm Alternative. [1-13].